TASAWUF DI SUMATERA SELATAN DARI ABAD KE-18 HINGGA ABAD KE-21 - Idrus Al-Kaf (Jurnal Ilmu Agama: Mengkaji Doktrin, Pemikiran, dan Fenomena Agama, 2019)
Sufism in Indonesia is not only Sunni, but also philosophical. This is evident in the mystical teachings of Sufism that developed throughout the archipelago, including in the Southern of Sumatera region. Islam with a Sunni Sufism style is very strong since the beginning of its arrival in South Sumatra. This can be traced to political and cultural contacts between Palembang and Java - where Wali Songo lived. While the main characteristic of South Sumatra's mysticism is its attachment to the tarekat - in this case, especially the Sammaniyah order. Even in the 20th century, when the flow of Islamic puritanism oriented to the mere outward aspects of religion increasingly thickened, the Sammaniyah order which had become part of the customs of the Palembang people could still be maintained.